2018
DOI: 10.1029/2018jd028623
|View full text |Cite
|
Sign up to set email alerts
|

The South Asian Monsoon Response to Remote Aerosols: Global and Regional Mechanisms

Abstract: The South Asian summer monsoon has been suggested to be influenced by atmospheric aerosols, and this influence can be the result of either local or remote emissions. We have used the Hadley Centre Global Environment Model Version 3 (HadGEM3) coupled atmosphere-ocean climate model to investigate for the first time the centennial-scale South Asian precipitation response to emissions of sulfur dioxide (SO 2 ), the dominant anthropogenic precursor of sulfate aerosol, from different midlatitude regions. Despite the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 53 publications
(63 reference statements)
4
33
1
Order By: Relevance
“…The anomaly from SSP5-8.5 is also significantly larger than that from SSP2-4.5. This suggests that anthropogenic aerosol plays a limited role in the evolution of global mean near-surface temperature on these timescales, supporting the conclusions of Shindell and Smith (2019). However, as will be discussed in Sect.…”
Section: Global Responsesupporting
confidence: 76%
See 2 more Smart Citations
“…The anomaly from SSP5-8.5 is also significantly larger than that from SSP2-4.5. This suggests that anthropogenic aerosol plays a limited role in the evolution of global mean near-surface temperature on these timescales, supporting the conclusions of Shindell and Smith (2019). However, as will be discussed in Sect.…”
Section: Global Responsesupporting
confidence: 76%
“…For precipitation, the regional response is particularly pronounced for the Asian summer monsoon (Levy et al, 2013;Westervelt et al, 2015;Acosta Navarro et al, 2017;Bartlett et al, 2018;Samset et al, 2018). Here, precipitation is sensitive to changes in remote aerosol through its control on the interhemispheric temperature gradient and intertropical convergence zone (ITCZ) location and the atmospheric wave pattern over Eurasia and to local aerosol changes, which further modify the local monsoon circulation (Polson et al, 2014;Dong et al, 2016;Guo et al, 2016;Shawki et al, 2018;Undorf et al, 2018). A number of studies have suggested that historical aerosol increases are a key driver of the observed decrease in Asian summer monsoon precipitation (Lau and Kim, 2010;Song et al, 2014;Li et al, 2015;Liu et al, 2019), and projected increases in precipitation due to aerosol reductions are consistent with this.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several faculty members of IISc have been experts at various Assessement Reports of the IPCC (past and present). Publications from the IISc in the period July 2018 -June 2019 include: South asian monsoon response to remote aerosols 41 . Research at IISc Connected with climate change, monsoon etc., is also going on in its Centre for Atmospheric and Oceanic Sciences (CAOS), its Centre for Earth Sciences (CEaS), and the Centre for Sustainable Technologies (CST), in addition to the Divecha Centre (DCCC).…”
Section: Climate Change Education and Research Training In Indiamentioning
confidence: 99%
“…Which is fine, given the focus of the paper on fast responses, but it is worth stressing this again here. The studies by Ganguly et al (2012) and Shawki et al (2018) provide nice insight into the differing fast and slow effects of aerosols on the South Asian monsoon, as well as the complementary global and regional mechanisms that are at play.…”
mentioning
confidence: 99%